Keratosis follicularis spinulosa decalvans: A dermoscopic perspective - Sudharani Chintagunta; Priyanka Jaju (Wolters Kluwer Medknow Publications, 2020)
Keratosis follicularis spinulosa decalvans (KFSD) is a rare follicular disorder characterized by widespread keratosis pilaris and progressive scarring alopecia of the scalp, eyebrows, and axillae. This condition is sometimes associated with photophobia and keratoderma. This is X-linked genodermatoses predominantly seen in males. It is unusual in females as they are carriers or have milder symptoms. Here, we report a dermoscopic perspective of this rare presentation of KFSD in an 11-year-old female.